Critical Path Analysis for Construction Schedule Optimization: RSGM UMSIDA Study Case - Izzul Manjulang Tunggal Panggayo; Andi Patriadi; Retno Hastijanti (jfpublisher, 2026)
The development of educational infrastructure represents a fundamental pillar supporting human resource advancement in Indonesia. Universitas Muhammadiyah Sidoarjo, as a growing higher education institution, addresses the need for academic facilities through the construction of a dental hospital (RSGM), demonstrating its commitment to public health services. This project functions as a teaching hospital in collaboration with the Faculty of Medicine at UMSIDA, enabling medical students to conduct clinical practice. This study aims to determine the optimal project duration after acceleration and identify the required costs resulting from this acceleration. The research applied the Critical Path Method (CPM) and Program Evaluation and Review Technique (PERT) to optimize construction scheduling. Results indicate that CPM effectively reduces project completion time from 147 weeks to 104 weeks, while PERT reduces it to 105 weeks, with additional costs of Rp 580,930,000.00 (3.85% of initial budget) and Rp 567,420,000.00 (3.76%) respectively. The PERT implementation, with critical path A-B-C-D-E-F-J, demonstrates a 99.99% probability of completing the project within 105 weeks. Overall, the acceleration efforts yield time savings of 43 weeks using CPM and 42 weeks using PERT, with PERT offering a more cost-efficient alternative. These findings validate the effectiveness of systematic network analysis approaches in educational healthcare facility construction, providing a replicable framework for similar infrastructure development projects in developing regions.